Students Perception towards Scaffolding Model in Reading of Junior High School - Muhilah Hasanah; Putri Kamalia Hakim (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
The purpose of this study was to determine students' perceptions of the scaffolding model in reading at Mts Al-Ajhariyyah. Based on the theory of Vygotsky Scaffolding is a structured learning support technique that is carried out at an early stage to encourage students to learn independently. Qualitative descriptive research methodology. Data collection techniques are observation and interviews. The research subjects were 3 8th grade students at Mts Al-Ajhariyyah. Data adapted from Benedict's Thesis (2016) and Sarkol's Thesis (2016). Data analysis used thematic analysis based on Braun and Clarke (2006). The result of student perception shows that students are motivated in learning English. Discussion of the scaffolding model in reading students can be independent and active in understanding reading. Students' reactions to the Scaffolding Model in learning show that it is very influential in learning English to foster student interest in learning English. The conclusion is that using the scaffolding model is easier and more effective for students to understand English learning in exploring English skills, especially reading. The researcher's suggestion is that the use of the scaffolding model for learning English is more effective in the classroom, and helps teachers to determine learning objectives during the teaching and learning process